Il progetto europeo Eucaland in corso di svolgimento: lo stato di avanzamento - Marzorati, Paola (Ri-Vista. Research for landscape architecture, 2015)
The EUCALAND Project, European Culture expressed in Agricultural Landscape, is part of the EU Culture Programme 2007. It runs with 42 partners from October 2007 to the end of 2009. The vision of the project is to consider the European Agricultural Landscape as part of our cultural heritage, including tha values and meaning they have for the people of Europe today. The final goal is to reach general recommendations on alternative ways to deal with our future agricultural landscapes, more culturally and sustainable oriented, addressed not only to scientists and planners, but also to policy makers and especially to the people of Europe.